Meningkatkan Kualitas Proses dan Hasil Pendidikan di Sekolah Binaan Terhadap Guru PAK - Simanjuntak, Pitna (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This research was conducted from July to December 2020 and was examined at 7 target schools at the advanced level of the Ministry of Religion of the city of Medan. Our supervisory targets in 2021 consist of 7 senior secondary level assisted schools and 21 teachers with civil servant status, permanent foundation teachers, foundation honor teachers and honorary teachers in public high schools. This supervision is limited to the target area and the distribution of teachers to each supervisor. The Medan city area consists of 21 districts, divided into 2 regions. Region I consists of 11 sub-districts, while Region II consists of 10 sub-districts. The division of this area is based on the number of Tk supervisors. Continued only 2 people. From the initial data obtained in research activities, it can be seen that 80% of teachers still have difficulties in arranging the time for learning activities, 85% are already present in coaching and giving their hearts to carry out tasks, 85% of teachers have not been able to make correct lesson plans The teachers still reach 90% who have been successfully fostered. Judging from the SNP monitoring, it can be seen that 85% of the school's attention is to maximize the available facilities. In terms of PKG, there are 85% of teachers who do not care about the identity of students. Keywords: learning outcomes; supervision  Abstrak: Penelitian ini dilaksanakan pada tujuh sekolah binaan tingkat lanjutan kemenag kota Medan. Adapun sasaran kepengawasan kami ditahun 2021 terdiri dari 7 sekolah binaan  tingkat lanjutan atas dan 21 orang guru berstatus PNS, Guru tetap Yayasan, Guru Honor Yayasan dan Guru  honorer di SMA Negeri. Kepengawasan ini dibatasi pada wilayah binaan dan pembagian guru pada masing-masing pengawas. Adapun wilayah kota Medan terdiri dari 21 kecamatan , dibagi menjadi 2 wilayah. Wilayah I terdiri 11 kecamatan sedangkan wilayah II terdiri dari 10 kecamatan Pembagian wilayah ini didasari jumlah pengawas Tk. Lanjutan hanya 2 orang. Dari data awal yang diperoleh pada kegiatan penelitian, terlihat bahwa 80% guru masih memiliki kesulitan dalam menyusun waktu kegiatan pembelajaran, 85% sudah hadir dalam pembinaan dan memberi hati untuk melaksanakan tugas, 85% guru belum dapat membuat RPP yang benar, maka dari segi pembinaan guru masih mencapai 90% yang berhasil dibina, Dikaji dari Pemantauan SNP terlihat  85 % perhatian pihak sekolah untuk memaksimalkan sarana yg tersedia, dari segi PKG terdapat 85% guru kurang perduli dengan identitas peserta didik . Kata Kunci: hasil belajar; pengawasan